Accelerating drug discovery efforts for trypanosomatidic infections using an integrated transnational academic drug discovery platform - Moraes, Carolina B.; Panecka-Hofman, Joanna; Wade, Rebecca C.; Pöhner, Ina; Müller, Wolfgang (SLAS discovery, 2019)
According to the World Health Organization, more than 1 billion people are at risk of or are affected by neglected tropical diseases. Examples of such diseases include trypanosomiasis, which causes sleeping sickness; leishmaniasis; and Chagas disease, all of which are prevalent in Africa, South America, and India. Our aim within the New Medicines for Trypanosomatidic Infections project was to use (1) synthetic and natural product libraries, (2) screening, and (3) a preclinical absorption, distribution, metabolism, and excretion-toxicity (ADME-Tox) profiling platform to identify compounds that can enter the trypanosomatidic drug discovery value chain. The synthetic compound libraries originated from multiple scaffolds with known antiparasitic activity and natural products from the Hypha Discovery MycoDiverse natural products library. Our focus was first to employ target-based screening to identify inhibitors of the protozoan Trypanosoma brucei pteridine reductase 1 (TbPTR1) and second to use a Trypanosoma brucei phenotypic assay that made use of the T. brucei brucei parasite to identify compounds that inhibited cell growth and caused death. Some of the compounds underwent structure-activity relationship expansion and, when appropriate, were evaluated in a preclinical ADME-Tox assay panel. This preclinical platform has led to the identification of lead-like compounds as well as validated hits in the trypanosomatidic drug discovery value chain.
Gesehen am 30.08.2019